INDIRECT INCITEMENT TO CRIME AND ITS IMPACT ON ESTABLISHING CRIMINAL LIABILITY: AN ANALYTICAL STUDY IN LIGHT OF IRAQI LEGISLATION, JURISPRUDENCE, AND JUDICIARY - Maher Tariq Abbas (PT. Antis International Publisher, 2026)
Objective: The aim of this research is to review the facets of